Physiological responses of cowpea simultaneously exposed to water deficit stress and varying light intensities at vegetative and reproductive growth stages (2022)
A combination of stresses as it occurs on the field poses more challenges to crop production than individual stress. Crops’ response to single stress also differs from that of combined stresses. The morpho-physiological responses of two cowpea varieties (IT89KD-288 and IT99K573-1-1) to a combination of stresses (water deficit stress and high light intensity) were investigated at different growth stages. Three levels of light intensities (L3: 259 Lux- 36%, L2: 394 Lux-55% and L1: 710.2 Lux-100%) were imposed using one, two and zero layer(s) of the net, respectively, while, water deficit stress at four levels (W1: no water stress; 0-5 bars, W2: moderate water stress; 5-15 bars, W3: moderately-severe; 15-40 bars and W4: severe water stress; 40-70 bars) was imposed differently at vegetative and reproductive growth stages. Data were collected on the cowpea yield, Leaf Temperature (LT), Chlorophyll (C), Photosynthesis (P), Stomatal Conductance (SC) and Canopy Transpiration Rate (CTR). Exposure to W4 under L1 considerably reduced cowpea yield by 80% compared to those grown under L3 and full watering. Reduced light intensity enhanced cowpea grain yield irrespective of water deficit stress and IT89KD-288 was superior to IT99K573-1-1. Reduction in light intensity also increased the SC from 55.18 in L1 to 76.88 in 36 % L3. Full light intensity without water stress (100% light intensity), increased C content, while severe water stress reduced the C content and CTR. Photosynthesis was, however, reduced under low light intensity compared to 100% light intensity. It was also observed that water deficit stress imposed at the reproductive stage did not affect P, CTR and SC unlike that of the vegetative stage. In conclusion, reduced light intensity enhanced cowpea tolerance to water deficit and increased yield. Cowpea response was dependent on growth stage, variety and severity of stress.